İZATİN TÜREVLERİNİN DNA KORUMA, ETKİLEŞİM ve ANTİMİKROBİYAL AKTİVİTESİNİN ANALİZLERİ ve SEFTRİAKSON-FENİLALANİN KOMBİNASYONUNUN SİNERJİSTİK ETKİLERİNİN DEĞERLENDİRİLMESİ - RAMADAN, Mohamed A. Ganim (Fen Bilimleri Enstitüsü, 2019)
Isatin, thiosemicarbazone and their derivatives, have been widely used in biological applications such as antimicrobial, antiviral and anticancer therapies. Herein, twentyseven isatin and thiosemicarbazone derivative compounds with 5-Fluoro-isatin and 5- Methoxy and metal complex were re-synthesized and evaluated for DNA binding analysis including DNA protection studies using plasmid DNA (pUC19) and DNA interaction experiments using Calf-Thymus DNA (CT-DNA). All compounds were also utilized in vitro assay to assess the antimicrobial activity of compounds against twentyone different pathogenic bacterial strains. All the synthesized compounds exhibited DNA protection activity which ranged from 11,7 to 59,5 % DNA protected. In general, among them, I3-(N-2-MP)-TSC had the greatest DNA protective activity. For DNA binding analysis, it was used for the isatin, thiosemicarbazone and their derivatives but not for the compounds with 5-Fluoro-isatin and 5-Methoxy complex. All compounds used for the DNA binding analysis had the same constant concentration (40 µM), which interacts with CT-DNA. It was also observed that DNA interactions gave a high intrinsic binding constant (Kb = 1,72 ×104 M −1 – 9,73 × 105 M −1 ). Besides, several derivatives of isatin thiosemicarbazone exhibited significant and selective antibacterial activity with low concentration. These compounds primarily affected Gram positive bacteria but were not effective against P. vulgaris and E. coli. The Gram positive methicillin-resistant S. aureus ATCC 43300 (MRSA) was the most influenced strain by these compounds. It was found that methyphenyl group at isatin was essential for its antibacterial activity for MRSA. The other compounds istain thiosemicarbazone combined with Fluoro-isatin and 5-Methoxy and metal complex inhibited Gram positive and Gram negative bacteria with mild to moderate inhibition zones. Some compounds contain nickel and zinc metals but there were no significant for increasing the antimicrobial activities or DNA protections. v Ceftriaxone belongs to the third-generation β-lactam antibiotics and it is useful for the treatment of a number of infectious diseases caused by both Gram positive and Gram negative bacteria. Phenylalanine is an essential aromatic amino acid of a human being, from which dopamine and norepinephrine neuro-transmitters are being synthesized. In the present study, we examined their combined efficacy against different types of pathogenic bacterial strains. The aim of this study designed to investigate the affect of Ceftriaxone combination with Phenylalanine on antimicrobial activates for both Gram positive and Gram negative bacteria that were including K. pneumonia, S. aureus ATCC 25923, P. vulgaris, E. coli, S. marcrescens, S. epidermis, Alpha haemolytics Streptococcus, E. faecium, P. aeruginosa, L. monocytogenes ATCC 7644, E. durans, S. kentucky, E. aerogenes ATCC 13048 and C. albicans ATCC 26555 were exposed to ceftriaxone and phenylalanine based on disk-diffusion method. Minimum inhibition concentration (MIC) was determined with ceftriaxone. Then 1mM ceftriaxone and 1mM phenylalanine solutions were mixed and observed greater zone of inhibition than ceftriaxone or phenylalanine alone against above mentioned bacterial strains. These results might open up a new avenue for using phenylalanine in combination with ceftriaxone to lower MIC level for better antibacterial effect, to reduce side effects of antibiotics, and to reduce emerging threats of antibiotic resistance bacteria. In this study, the combined use of phenylalanine and ceftriaxone has revealed increased antimicrobial sensitivity against some selected both Gram positive and Gram bacteria in vitro
Keywords: Isatin thiosemicarbazone derivatives, 5-Fluoro isatin, 5-Methoxy isatin, Antimicrobial activity, DNA binding analysis, DNA protections